2020
DOI: 10.22271/chemi.2020.v8.i2l.8856
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and delineation of micronutrient pools in some selected Inceptisols and Alfisols of West Bengal

Abstract: The present study has been conducted to determine the cationic micronutrient (Zn, Cu, Fe, Mn) pools based on other factors towards plant availability in 20 selected soil series (10 series each from Alfisols and Inceptisols) of West Bengal. Apart from physicochemical characterization, the soils were sequentially extracted for different fractions such as the water-soluble and exchangeable (SE); organically bound (OB); manganese oxide-bound / occluded (MnOx), amorphous iron oxide-bound (Am_FeOx), crystalline oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(89 reference statements)
1
1
0
Order By: Relevance
“…The highest concentration of total Cu was in Alfisol-I (72.2 mg/kg), whereas the minimum in Entisol-I (44.4 mg/kg). The findings of the present investigation were lined with the findings of Bhattacharya et al (2020). The mobility of Cu in various soil orders represent as: Vertisol-I>Vertisol-II>Inceptisol-I>Inceptisol-II>Entisol-II>Entisol-I>Alfisol-I>Alfisol-II (Table 1).…”
Section: Copper Fractions and Its Mobility Factorsupporting
confidence: 89%
See 1 more Smart Citation
“…The highest concentration of total Cu was in Alfisol-I (72.2 mg/kg), whereas the minimum in Entisol-I (44.4 mg/kg). The findings of the present investigation were lined with the findings of Bhattacharya et al (2020). The mobility of Cu in various soil orders represent as: Vertisol-I>Vertisol-II>Inceptisol-I>Inceptisol-II>Entisol-II>Entisol-I>Alfisol-I>Alfisol-II (Table 1).…”
Section: Copper Fractions and Its Mobility Factorsupporting
confidence: 89%
“…In case of total Zn content, Alfisol-I (93.3 mg/kg) recorded the maximum value, whereas the lowest in Entisol-I (57.3 mg/kg). Bhattacharya et al (2020) reported that total Zn content was higher in Alfisol as compared to Inceptisol and Entisol. Zinc was highly mobile in Vertisol-I, as it observed the highest MF 1.81% (Table 1) and the mobility factor of Zn follows the order of Vertisol>Inceptisol>Entisol>Alfisol.…”
Section: Resultsmentioning
confidence: 96%